Appendicitis During Pregnancy: Diagnostic Challenges and Fetal Outcomes - Umm E Habiba; Asad ur Rehman; Mahmood, Sana; Qaisar, Hafiza Aqsa; Riaz, Usama; Khan, Rana Ali Haider (Indus Journal of Bioscience Research, 2025)
Background: Acute appendicitis is the most common non-obstetric surgical emergency during pregnancy, posing unique diagnostic and therapeutic challenges. Objective: To evaluate the clinical presentation, diagnostic accuracy of imaging modalities, and the maternal and fetal outcomes associated with appendicitis during pregnancy. Methods: This retrospective observational study was conducted at Department of Obstetrics and Gynaecology, DHQ Hospital Okara City, Okara, Pakistan, from Feb 2024 to Feb 2025. A total of 85 pregnant women who were diagnosed and treated for acute appendicitis during pregnancy were included in the study. Patients were identified from hospital surgical records, obstetric databases, and operative notes. Data were collected retrospectively using a standardized data abstraction form. Demographic variables including maternal age, parity, and gestational age at presentation were documented. Clinical presentation was analyzed based on symptoms including abdominal pain, nausea, vomiting, anorexia, and fever. Results: The majority of patients presented in the second trimester (43%). Abdominal pain was the most common symptom (100%), with right upper quadrant pain noted in 26.2% of cases. Ultrasound confirmed appendicitis in 67.2% of cases, while MRI showed higher diagnostic accuracy (83.3%). Laparoscopic surgery was performed in 63.1% of patients and was associated with fewer complications and shorter hospital stay compared to open surgery. Fetal loss occurred in 9.2% of cases, most commonly associated with appendiceal perforation and delayed diagnosis. Logistic regression identified perforated appendix (OR: 4.8, p = 0.004) and diagnostic delay >48 hours (OR: 3.9, p = 0.01) as significant predictors of fetal loss. Conclusion: It is concluded that early recognition and timely surgical intervention in appendicitis during pregnancy are essential to improving maternal and fetal outcomes. MRI should be considered when ultrasound is inconclusive. Perforation and diagnostic delay significantly increase the risk of fetal loss, emphasizing the need for prompt clinical evaluation and decision-making in pregnant patients presenting with abdominal pain.